2007
DOI: 10.1111/j.1532-5415.2007.01244.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of tai chi for the Prevention of Falls: The Central Sydney tai chi Trial

Abstract: Participation in once per week tai chi classes for 16 weeks can prevent falls in relatively healthy community-dwelling older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
176
1
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(197 citation statements)
references
References 27 publications
9
176
1
11
Order By: Relevance
“…However, although this study was carried out with a high-risk population, the participants had only minor balance problems and low fear of falling at the outset which may have influenced the study findings. More recent work by Voukelatos et al amongst fairly healthy older adults has suggested that falls can be reduced with Tai Chi compared with controls, in those who have had two or more falls, but not those who had one or more [93].…”
Section: Falls/fear Of Fallingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although this study was carried out with a high-risk population, the participants had only minor balance problems and low fear of falling at the outset which may have influenced the study findings. More recent work by Voukelatos et al amongst fairly healthy older adults has suggested that falls can be reduced with Tai Chi compared with controls, in those who have had two or more falls, but not those who had one or more [93].…”
Section: Falls/fear Of Fallingmentioning
confidence: 99%
“…Again, evidence is limited, with the majority of existing studies focusing on improved balance and less evidence examining the impact on muscle strength in older adults. Nevertheless, RCTs have suggested that, in a relatively short period, Tai Chi can help to maintain and improve functional balance and provide overall physical gains [25,[91][92][93]]. …”
Section: Strength and Balancementioning
confidence: 99%
“…5,6 Group-based Tai Chi has been found to be effective for falls prevention in several trials. 9,10 Other well-designed group-based interventions can also prevent falls. 11,12 The availability of home-based programs is also important as many older people are reluctant to or unable to attend group exercise classes.…”
mentioning
confidence: 99%
“…No presente trabalho, foram empregados cinco testes diferentes na avaliação do equilíbrio, à semelhança do estudo de Voukelatos et al 13 , que aplicaram uma bateria de seis testes visando diferentes aspectos dessa variável. Esses autores constataram benefícios significativos do TCC (praticado no estilo Sun, uma hora por semana) sobre o desempenho dos praticantes em todos os testes -com exceção do TAF -, assim como a redução no número de quedas.…”
Section: Capacidade Funcionalunclassified